Remoção simultânea de matéria orgânica e nitrogênio em um reator de leito estruturado submetido à aeração intermitente: efeito do diâmetro do material suporte e da porosidade do meio - Souza, João Vitor Rodrigues De (2020)
The present work determined the effect of water level and air flow on oxygen transfer in a reactor. Such characterization was made through the estimation of the oxygen transfer coefficient parameters (KLa), standard oxygen transfer rate (SOTR) and standard oxygen transfer efficiency (SOTE). An experimental of the center faces (DCF) was used. In this design, a total of 11 tests were carried out, varying the air flow (2, 4 and 6 L,min-1) and the water level in the reactor (20, 40 and 60 cm). The results indicated that there was a significant effect of the variables on the DO concentration in the system, with the system achieving its best performance when operated with an air flow of 5 L,min-1 and water level in the 40cm reactor. However, through the regression test and lack of adjustment F, it was possible to conclude that the models were significant non-predictive, requiring that further studies addressing another range of operation be performed, so that such conclusions obtained can be used for future projections This study also evaluated the performance of a structured bed reactor subject to intermittent aeration (SBRIA) in the simultaneous removal of chemical oxygen demand (COD) and total nitrogen (TN) from a synthetic effluent. The reactor was operated under a hydraulic retention time (HRT) of 10h, air flow of 4.0 L.min-1 and aeration and non-aeration cycles of 2h/1h. An experimental Central Composite Designs (CCD) was used to define the diameter conditions of the support material and the porosity (factors) to be studied. Eight operating conditions, corresponding to the variation in the diameter of the support material (1, 2 and 3 cm) and porosity (60, 70 and 80%), were tested. Response surface methodology was used to analyse the influence of the factors above the results, the removal of TN and COD. It was observed that the factors had no significant effect on the results and efficiency of COD removal and nitrification, with a 95% confidence level, obtaining values, respectively, above 80% and 90% in all conditions. tested. The best results of denitrification efficiency and TN removal were obtained when the system was operated with a support material diameter equal to 3 cm and porosity of 60%. The response surface demonstrated that the effect of increasing the diameter of the support material coupled with the reduction of porosity was positive under the denitrification efficiency, favoring the existence of an anoxic zone inside the foam and, consequently, generating an effluent with low concentrations. from NO3-.